PENGELUARAN WAJIB PAJAK DALAM PENINGKATAN PENERIMAAN PERPAJAKAN DI KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR UTARA - Dharmawati (Paulus Law Journal, 2021)
Taxpayer Compliance in Increasing Tax Revenue at the North Makassar Primary Tax Service Office. The purpose of this study is to determine taxpayer compliance, tax receipts, general provisions and tax procedures that affect taxpayer compliance after the enactment of Law Number 16 Year 2009. This study uses a juridical type of research normative. Primary and secondary data sources and tertiary. This research was analyzed qualitatively by describing descriptively the results of existing data. The results showed that the compliance of taxpayers at the North Makassar Primary Tax Service Office was not yet compliant optimally, although in quantity the tax revenue increased from year to year. The reason is the lack of knowledge and understanding of taxpayers, inadequate tax human resources as well as negative taxpayers regarding tax provisions have not been evenly distributed. While the factors that influence taxpayer compliance are legal substance factors, legal structure factors, legal cultural factors and tax socialization factors.